1991
DOI: 10.1021/tx00020a017
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, physical, and toxicological characterization of fumes produced by heating tetrafluoroethene homopolymer and its copolymers with hexafluoropropene and perfluoro (propyl vinyl ether)

Abstract: Submicrometer solid-particle (fume) aerosols with up to about 10(8) particles/cm3 are formed when dilute vapors of low molecular weight (MW) (ca. 5000-10,000) perfluoro polymers condense in air. The aerosol (e.g., 0.2 mg/m3) formed from these vapors is highly toxic to laboratory rats by inhalation (30-min exposure) when fresh but loses toxicity in minutes, apparently owing to coagulation. These fumes may result from (a) pyrolysis of tetrafluoroethene homopolymer or tetrafluoroethene-hexafluoropropene copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…Although these data are consistent with our hypothesis that inhaled ultra ne particles have a signi cantly greater toxic and in®ammatory potential than larger sized particles, it cannot be excluded that the ageing and coagulation of the fresh PTFE fumes for several minutes had altered potential short-lived toxic radicals on the surface of the particles (Pryor et al 1990). Whether the existence of such radicals plays a role in the toxicity of freshly generated polymer fumes is uncertain; earlier studies have shown that fumes generated from di¬erent plastic materials all show high toxicity regardless of the presence or absence of short-lived radicals (Seidel et al . 1991).…”
Section: (B) E® Ect Of Ageing On Ptfe Toxicitysupporting
confidence: 82%
“…Although these data are consistent with our hypothesis that inhaled ultra ne particles have a signi cantly greater toxic and in®ammatory potential than larger sized particles, it cannot be excluded that the ageing and coagulation of the fresh PTFE fumes for several minutes had altered potential short-lived toxic radicals on the surface of the particles (Pryor et al 1990). Whether the existence of such radicals plays a role in the toxicity of freshly generated polymer fumes is uncertain; earlier studies have shown that fumes generated from di¬erent plastic materials all show high toxicity regardless of the presence or absence of short-lived radicals (Seidel et al . 1991).…”
Section: (B) E® Ect Of Ageing On Ptfe Toxicitysupporting
confidence: 82%
“…The agglomerates from Teflon are likely a result of the formation of Teflon polymer fragments from the pyrolysis of Teflon. Seidel et al (1991) found that nominal 10 4 Dalton Teflon polymer fragments are formed from the pyrolysis of Teflon over the same temperature range as our experiments with Teflon. These fragments apparently grow through nucleation/condensation/coagulation to form nominal 30 nm solidlike spherules.…”
Section: Chemical Basis For Smoke Particle Morphologysupporting
confidence: 75%
“…The physical conditions in these tests are usually not well defined (as to temperature, contact time, flow rate, oxygen depletion, etc.). In~, the primary low temperature toxic component is a polymer fragment (Waritz and Kwon 1968;Seidel et al 1991). Temperatures at which this is important (below 450°C) and the relatively low degree of polymerization during c-CdF8 pyrolysis suggest that this is not likely to be a problem with C-C4F8.At higher temperatures, PTFE pyrolysis products are very similar to those of C-C4F8, so some relevant qualitative comparisons might be drawn.…”
Section: Toxicitymentioning
confidence: 99%
“…A series of PTFE fire studies (Baker and Kaiser 1991;Seidel et al 1991), was conducted in an attempt to duplicate earlier very high toxicity results (Levin et al 1982). Baker and Seidel concluded that the National Bureau of Standardstoxicity was dueto the formationof toxic particulate under fairly special conditions, namely those in which polymer degradation fumes are heated and reheated in a hot furnace without an actual flame.…”
Section: Descriptive Chemistrymentioning
confidence: 99%